Digital finance in the EU - Beck, Thorsten,Giani, Leonardo,Sciascia, Giuseppe (European University Institute, 2023)
This e-book contains contributions on some of the main topics covered in the training activities which took place during the first academic year of the EU Supervisory Digital Finance Academy (EU-SDFA), either at the European University Institute (EUI) or in workshops hosted by the European Supervisory Authorities (ESAs). The EU-SDFA is a technical support project launched by the European Commission (DG REFORM) in October 2022, in cooperation with DG FISMA, the ESAs and the Florence School of Banking and Finance (Robert Schuman Centre, EUI). The e-book consists of twelve contributions from different authors grouped in three broad areas: overview of the main initiatives taken at European Union level and the challenges and perspectives from a global viewpoint; the main technologies and drivers of digital finance; the main risks and opportunities involved in digital finance. The e-book is intended to enable past and future EU-SDFA participants to complement their learning experiences, while also providing valuable documents to readers interested to get an understanding of the interplay between digital finance and supervision.
10.2870/51343
Keywords: Graue Literatur; Amtliche Publikation; Aufsatzsammlung; Finanzdienstleistung; Digitalisierung; EU-Staaten; financial technology; blockchain; artificial intelligence; innovation; central bank; information warfare; sustainable development; business model; European Union; case study